BRASS score and complex discharge: a pilot study - Cammilletti, Valentina; Forino, Fortunata; Palombi, Marina; Donati, Daniele; Tartaglini, Daniela; Di Muzio, Marco (Acta Biomedica Atenei Parmensis, 2018)
Aims: A highly functional continuity of patient care, which is linked to the reduction of the risk of long-term hospitalization, above all for ‘at-risk’ patients. Research into an objective, reliable instrument for redirecting individual results to organizational aims to extend the entire country, is a fundamental step to move from a reactive assistance approach to a pro-active one. Methods: An observational and descriptive retrospective study was carried out July - November 2014 in two Italian state hospitals, completing the BRASS Index within 48/72 hours of admission. Results: The study group consisted of 122 inpatients. A correlation presented itself, albeit low (ñ=0.05191), between age and the number of ‘revolving door’ admissions; a medium correlation (ñ=0.485131) between age and risk band (according to BRASS). Conclusions: The BRASS Index is straightforward and swift, and can prove a valuable tool in directing nurses’ attention to those patients most at risk of prolonged hospitalization.